School Management in Enhancing Teacher Professionalism at SMP Negeri 8 Muaro Jambi - Maisah Maisah; Muhajirin Muhajirin; Fadhlilah Fadhlilah; Husin Husin (Universitas Muhammadiyah Enrekang, 2024)
This study aims to analyze school management in enhancing teacher professionalism at SMP Negeri 8 Muaro Jambi. The principal plays a crucial role as a motivator and facilitator in supporting teachers’ competency development through internal training, seminars, webinars, and independent training via the SIM PKB platform. The study adopts a qualitative approach using a case study method. Data were collected through in-depth interviews with the principal, teachers, and administrative staff, as well as direct observations of school activities. The findings indicate that the school's management strategies include activating learning communities (KOMBEL), direct observation of the learning process, and collaboration with PGRI and assigned supervisors to organize in-school training. While these programs are effective, the study also identified challenges in their implementation, such as varying levels of teacher motivation, time constraints, limited IT skills, and insufficient supporting facilities. Additionally, ineffective communication in conveying information about professional development programs was found to be an obstacle. The study concludes that the role of the principal as a motivator and facilitator significantly impacts improving teacher professionalism. Moral support, incentives, and relevant training can enhance teachers’ skills and the quality of learning. Thus, effective school management can positively influence student learning outcomes and foster a more dynamic and interactive learning environment. Recommendations are provided to improve communication strategies and incentive support to optimize teacher participation in professional development.